Estimation of Optimal and Maximum Standardized Ileal Digestible Methionine Requirements Based on Performance for Male Broilers Aged 0 to 21 Days - Su-Hyun An; Changsu Kong (Animals)
Two experiments were conducted with Ross 308 male broiler chickens to determine the standardized ileal digestible (SID) methionine (Met) requirement for maximum weight gain during the starter (0 to 10 days) and grower (10 to 21 days) phases. A total of 720 and 288 birds were allocated to Experiments 1 and 2, respectively, and assigned six dietary treatments in a randomized complete block design. The experimental diets were formulated with corn, soybean meal, and synthetic amino acids to achieve varying SID Met levels (3.8 to 5.8 g/kg in experiment 1 and 3.0 to 5.5 g/kg in experiment 2), with increments of 0.4 and 0.5 g/kg. Weight gain, feed intake, and the gain-to-feed ratio (G:F) increased quadratically (p < 0.05) as dietary SID Met increased. The SID Met requirements for maximum weight gain and G:F in the starter phase were 5.1 g/kg (79.5 mg/d) and 5.3 g/kg (89.8 mg/d), while in the grower phase, they were 5.5 g/kg (343.0 mg/d) and 5.4 g/kg (330.3 mg/d), respectively. These findings, divided into two growth phases, provide guidelines to facilitate the optimal and maximum performance of young male broilers, and this may facilitate the selection of appropriate values for formulating broiler feed. These findings also highlight the importance of Met supplementation strategies for improving performance.